2009
DOI: 10.1002/bjs.6606
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of pancreatic surgery for metastatic renal cell carcinoma

Abstract: The actuarial 5-year overall survival rate following pancreatic surgery for RCC metastases was 72.6 per cent, as determined by pooled analysis from published series. Extrapancreatic disease was an independent risk factor for recurrence, but had no significant impact on overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 129 publications
6
125
1
4
Order By: Relevance
“…In general, metastasectomies for synchronous metastases are associated with shorter median survival than resection of metachronous metastases; this has been shown in the case of hepatectomy for colorectal metastases [28,29], pulmonary resection for RCC metastases [30] and adrenalectomy for metastatic non-small-cell lung cancer [31]. The previously-mentioned review of case reports and series of pancreatectomy for metastatic RCC suggest that the same principle applies [27]; our data are not consistent with this, but a dedicated study looking specifically at this question remains to be performed. The reason for this association between synchronous metastases and shorter overall survival following metastasectomy remains to be elucidated-it may indicate a more aggressive underlying biology in the primary tumour, or else reflect the increased morbidity following resection of both the primary and the metastasis either simultaneously or in quick succession.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In general, metastasectomies for synchronous metastases are associated with shorter median survival than resection of metachronous metastases; this has been shown in the case of hepatectomy for colorectal metastases [28,29], pulmonary resection for RCC metastases [30] and adrenalectomy for metastatic non-small-cell lung cancer [31]. The previously-mentioned review of case reports and series of pancreatectomy for metastatic RCC suggest that the same principle applies [27]; our data are not consistent with this, but a dedicated study looking specifically at this question remains to be performed. The reason for this association between synchronous metastases and shorter overall survival following metastasectomy remains to be elucidated-it may indicate a more aggressive underlying biology in the primary tumour, or else reflect the increased morbidity following resection of both the primary and the metastasis either simultaneously or in quick succession.…”
Section: Discussionmentioning
confidence: 89%
“…A thorough systematic review in 2009 examined all available case reports and patient series of RCC with pancreatic metastases available at that time, and concluded that patients with such metastases who are fit for surgery should be considered for curative resection [27]. The authors cautioned that patients with early multi-organ metastases might be better managed with observation and neoadjuvant therapy, as early recurrence seemed to predict a more aggressive clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72] Cumulative data suggest that pancreatic metastasectomy might be benefi cial in patients with good performance status and one metastatic site. 73 However, 2·8% inhospital mortality after extensive surgery, done as pancreaticoduodenectomy in 35·8% of patients and total pancreatectomy in 19·9% of patients, suggests that morbidity and mortality might outweigh the potential benefi t. In view of the overall low quality of the data, and the substantial surgical morbidity, patients with a short interval to pancreatic metastasis after nephrectomy may be best treated with systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of them are from clear cell type [26][27][28], and they often present years after initial treatment [9, 10,12].…”
Section: Discussionmentioning
confidence: 99%
“…They can either present as part of disseminated disease or as isolated metastases. Historically, disease response and survival rates in patients on immunotherapy-type systemic therapy have been disappointing [2][3][4][5][6][7][8], and surgical metastasectomy has been advocated in patients with resectable disease as they have shown superior outcomes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%